Internet Addiction Leads to Loneliness or Loneliness Leads to Internet Addiction? - Triana Budi Lestari (Jurnal Psikiatri Surabaya, 2024)
Introduction: Internet users in Indonesia are growing from year to year. Based on the latest data from the Indonesian Internet Service Provider Association, known as Asosiasi Penyelenggaraan Jasa Internet Indonesia (APJII), in 2022, internet users in Indonesia reached 210 million. With a large number of internet users, there are positive and negative consequences that occur. Internet addiction began to be studied by many researchers. These studies include research on the factors that cause internet addiction, as well as its correlation with loneliness. To explain the correlation between internet addiction and loneliness. Methods: Literature review. Results: Loneliness is a complex and usually unpleasant emotion that is thought to be a factor in individuals experiencing internet addiction. Loneliness is the thought of loss and dissatisfaction that occurs due to a mismatch between the individual’s social interaction and the social interaction one expects. Hence to overcome the loneliness that is felt, individuals express themselves better in cyberspace than in person. Internet addiction is a condition in which internet users use the internet excessively, due to a lack of self-control and interferes with their daily tasks and functions, to the detriment of themselves. This sums in several negative consequences. Studies showed that internet addiction and loneliness are correlated and mutually reinforcing. Conclusions: The relationship between loneliness and internet use is bidirectional in the sense that just as the internet may drive individuals towards loneliness, loneliness can also encourage individuals to spend more time on the internet. Keywords: Internet Addiction, Loneliness